Syrup cellular penetration and histological study of candied mango (Mangifera indica Linn.) - Acu, Ma Victoria S; De Leon, Son. (1984., 1984)
Three osmotic dehydration procedures namely: 40-50-60°Bx step-up method; 60°Bx direct immersion and addition of dry sugar were evaluated by determining the solute uptake-water loss behavior, syrup cellular penetration and cellular changes by histological studies on the tissue. Solids gain was found to be the highest in the 40-50-60°Bx method and lowest in the 60°Bx method. Moisture loss and weight loss was highest in the dry sugar and lowest in the 60°Bx method. Syrup cellular penetration, after equilibriation was deepest in the step-up process followed by the dry sugar method then the 60°Bx direct immersion. Histological study generally showed cell distention and a reduction in the thickness and discontinuity of cell walls in fruit slices soaked in hot syrup while the addition of dry sugar caused plasmolytic effects and contraction of the protoplasmic constituents from the cell
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mango -- Preserva; Mango, Can